Características Termo-Higrométricas em Bairros com Diferentes Padrões Construtivos em Presidente Prudente - SP - Bovis, Renan Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This study aimed to analyze the characteristics of temperature and air humidity from neighborhoods of Presidente Prudente according to the pattern of land use specific to each of them, over a representative period of winter (July 2011), at different times of day in order to identify the major changes in climatic elements and their causes in urban areas. The work is based mainly on the Monteiro’s theory (1976) of Urban Climate System and for its implementation was used data of temperature and relative humidity of the air in three urban neighborhoods and one rural area. With them, a Chart of Rhythmic Analysis was elaborated for identification of the operating atmospherics systems and basic climate conditions in the period. Were prepared, also, graphs and charts to evaluate and compare the data. There were significant differences in the characteristics of temperature and air humidity between the neighborhoods, especially when compared the urban areas with the rural area

Este trabalho teve o objetivo de analisar as características termo-higrométricas de bairros de Presidente Prudente de acordo com o padrão de utilização do solo específico de cada um deles, durante um período representativo de inverno (julho de 2011), em diferentes horários do dia, a fim de se identificar as principais alterações nos elementos climáticos e seus causadores em áreas urbanas. O trabalho se fundamenta, principalmente, na teoria do Sistema Clima Urbano, de Monteiro (1976) e para sua execução foram utilizados dados de temperatura e umidade relativa do ar de três bairros urbanos e uma área rural. Com eles foram elaborados um Gráfico de Análise Rítmica para identificação dos sistemas atmosféricos atuantes e das condições do clima no período. Foram elaborados, também, gráficos e tabelas para avaliação e comparação dos dados. Foram constatadas diferenças significativas nas características termo-higrométricas entre os bairros, principalmente quando comparadas as áreas urbanas com a área rural
Keywords: Geografia; Solo e clima; Temperatura; Solos - Umidade; Solo - Uso